507 mechanical movements - Brown, Henry T.; Brown, Henry T. (Mineola, New York : Dover Publications, 2005)
"This 1868 compendium of ingenious mechanisms employs simple drawings to explain 507 of the small components that constitute complex machinery. Left-hand pages feature illustrations, and facing pages offer brief descriptions of use and operation. Ranging from simple to complex, the mechanisms include cranks, pulleys, drills, wheels, and screws."--Amazon.
Reprint: Originally published: Five hundred and seven mechanical movements. 19th edition New York : Brown and Seward, 1901.
Includes index.
Keywords: Mechanical movements